2020
DOI: 10.1159/000509953
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab-Induced Delayed-Onset Hepatitis

Abstract: Hepatitis is one of the serious immune-related adverse events (irAEs). However, delayed-onset hepatitis induced by immune-checkpoint inhibitors (ICIs) is rare, and the histopathological features remain to be clarified. A 65-year-old woman with advanced lung adenocarcinoma in the right upper lobe (cT4N3M1c, c-stage IVB) received four courses of pembrolizumab. Her hepatic and biliary tract enzyme levels started increasing 2 months after the final administration of pembrolizumab, and the elevated levels of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…Recently, new reports of irAEs emerging after discontinuation of immunotherapy, a clinical diagnostic complex termed delayed immune-related events (DIRE), have surfaced[ 9 ]. The first case of DIRE after discontinuation of pembrolizumab was reported in 2013[ 10 ], and various late-onset irAEs have also been reported in the literature[ 11 ]. Anti-PD-1 antibodies continue to bind to lymphocytes several weeks after the last infusion of PD-1 inhibitors, which explains the development of irAEs after discontinuation of ICI therapy[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new reports of irAEs emerging after discontinuation of immunotherapy, a clinical diagnostic complex termed delayed immune-related events (DIRE), have surfaced[ 9 ]. The first case of DIRE after discontinuation of pembrolizumab was reported in 2013[ 10 ], and various late-onset irAEs have also been reported in the literature[ 11 ]. Anti-PD-1 antibodies continue to bind to lymphocytes several weeks after the last infusion of PD-1 inhibitors, which explains the development of irAEs after discontinuation of ICI therapy[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The research from Nakamura et al in melanoma showed that the occurrence of endocrine irAEs was positively linked to baseline eosinophil counts (39). Multiple studies analyzing tissue biopsy samples from patients with hepatic irAEs have found massive infiltration of inflammatory cells, primarily CD8+ T lymphocytes and eosinophils (40)(41)(42)(43). Similarly, an autopsy analysis of a melanoma patient with multiple irAEs showed a marked increase of CD8+ T lymphocytes in involved organs such as the heart, brain, and lungs (6,44).…”
Section: Discussionmentioning
confidence: 99%
“…AIH and irAE hepatitis can be distinguished by immunostaining of lymphocytes [ 6 , [9] , [10] , [11] ]. AIH has predominantly CD20 + and CD4 + lymphocytes, whereas irAE has predominantly CD3 + and CD8 + lymphocytes [ 9 , [12] , [13] , [14] , [15] , [16] ].…”
Section: Discussionmentioning
confidence: 99%